Cultural violence and gender identities : a feminist post-structural discourse analysis of This House of Clay and Water - Raza, Amber; Rashid, Shaista; Malik, Sadia (Penerbit Universiti Kebangsaan Malaysia, 2022)
The present study explores the dialectic relation between gender, identity, violence, discourse and social practices, as portrayed in Mansab’s book This House of Clay and Water. Viewing gender as a biological trait determined at birth whereas all the social roles and identities are considered fixed is a prevalent social practice in countries like Pakistan. Proving that gender is a socio-cultural construct is the first step towards awareness that gender roles are not fixed and certain violent social norms can be transformed to help the marginalized groups like intersex/transgenders, and women. This study aims to show that certain forms of abuse, repression and cultural violence are normalized through the use of language and literary discourses, and the very same tools can be used to counter these structures. The theoretical insights for this research are drawn from Feminist post-structural discourse Analysis and Butler’s Queer theory. The qualitative analysis is based on the closed textual reading and discourse analysis within the parameters of the chosen framework. The significance of this study lies in the fact that it applies FPDA to study fictional characters who are a reflection of humans and social practices in general, and how they are forced to suffer and ultimately resist gender-based violence to co-construct their ever-shifting identities through discourse.